Students' Evaluation of Their Experiences with Project-Based Learning in a 3D Design Class - Mou, Tsai-Yun (The Asia-Pacific education researcher, 2020)
This study investigated college students’ experiences with project-based learning in 3D design, specifically for 3D modeling. A total of 49 college students from a Visual Arts program participated in this study. By implementing a project-based assignment throughout one semester, each student was responsible for completing his or her proposed design. In-class and out-of-class complementary methods were implemented throughout the semester. Focus group interviews were conducted to examine students’ use of self-regulated learning methods and experiences with project-based learning in the class. The results revealed that adopting PBL with complementary methods was helpful for developing students’ practical capacity and self-regulated learning attitude. The students used a combination of self-regulated learning methods in their projects, including other resources, online materials, problem notes, sharing activities, project diaries, and personal schedules. Their experiences with project-based learning were mainly related to motivation, sharing and feedback, and the teaching approach in the class. Some students expressed thinking of self-efficacy, problem solving, and reflection and self-assessment in the class. In general, the students showed more interest in 3D design, and higher motivation to complete the project. The project achievement promoted students’ confidence, practical skills, interest in the subject, and most importantly, their self-regulated learning attitude.